Cocoa Bean Cleaner and Dryer Device: A Microcontroller Experiment - Mohammad Hafiz Hersyah*; Desta Yolanda; Nela Fatma (Aceh International Journal of Science and Technology)
Cleaning and drying cocoa beans are generally done manually by farmers. The manual cleaning process takes a long time, and the pulp reduction is not optimal. In contrast, drying using sunlight takes a long time when it is done in the rainy season. This causes the cocoa beans to be moldy and have low sale value. In the equipment made by the factory, the two machines are made separately and are hardly affordable by the farmers. Based on these problems, a microcontroller-based cocoa bean dryer (de pulper) was designed with a single container so that both processes could be carried out using just one machine. To elaborate this system, cleaning is carried out on fermented cocoa beans that are pulp shed in a rotating cylinder. In comparison, the drying process is carried out by using a heat source, a soil moisture sensor to detect the moisture content of cocoa beans, a DS18B20 sensor to detect temperatures in the drying container, and a cylindrical container is rotated using an A.C. motor. Based on the experiment results, it takes 10 minutes to clean the cocoa beans from the pulp. The drying process takes 5 hours, 10 minutes, and 5 hours and 40 minutes to dry the cocoa beans to a maximum moisture content of 7%. A rotating drying container can speed up the drying process of cocoa beans compared to drying using sunlight in the rainy season. The proposed tool in this study can carry out more efficient capacity better than the conventional tool.